2017
DOI: 10.1093/eurheartj/ehx736
|View full text |Cite
|
Sign up to set email alerts
|

Left atrial function to identify patients with atrial fibrillation at high risk of stroke: new insights from a large registry

Abstract: The assessment of LA reservoir strain and PA-TDI on echocardiography after initial CHA2DS2-VASc scoring provides additional risk stratification for stroke and may be useful to guide decisions regarding anticoagulation for patients upon first diagnosis of AF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
75
1
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(84 citation statements)
references
References 40 publications
3
75
1
5
Order By: Relevance
“…Hypertension and even high-normal blood pressure is a risk factor for developing AF and recent guidelines for the management of arterial hypertension clearly state that AF should be considered a manifestation of hypertensive heart disease [ 4 ]. LA function might also be linked to the cardioembolic risk profile in patients with AF and can even provide incremental value for embolism risk stratification over CHA2DS2-VASc score [ 5 , 6 ]. Recently announced EACVI AFib Echo Europe Registry for assessing relationships of echocardiographic parameters with clinical thrombo-embolic and bleeding risk profile in non-valvular AF aims to determine echocardiographic parameters stratifying prognosis and improving management in categories of AF patients.…”
Section: Introductionmentioning
confidence: 99%
“…Hypertension and even high-normal blood pressure is a risk factor for developing AF and recent guidelines for the management of arterial hypertension clearly state that AF should be considered a manifestation of hypertensive heart disease [ 4 ]. LA function might also be linked to the cardioembolic risk profile in patients with AF and can even provide incremental value for embolism risk stratification over CHA2DS2-VASc score [ 5 , 6 ]. Recently announced EACVI AFib Echo Europe Registry for assessing relationships of echocardiographic parameters with clinical thrombo-embolic and bleeding risk profile in non-valvular AF aims to determine echocardiographic parameters stratifying prognosis and improving management in categories of AF patients.…”
Section: Introductionmentioning
confidence: 99%
“…Основным субстратом фибрилляции предсердий (ФП) является структурно-функциональная перестройка левого предсердия (ЛП), выраженность которой прямо связана как с утяжелением клинического варианта течения аритмии [1], так и с развитием ее осложнений -инсульта [2,3], хронической сердечной недостаточности [4] и смерти [3,5]. Поэтому особенностям ремоделирования ЛП в различных клинических ситуациях и факторам, приводящим к его развитию, уделяется особое внимание [6].…”
Section: Left Atrial Phasic Function фазовый анализ функции левого прunclassified
“…In support of this concept, LA enlargement, usually defined as anterior–posterior LA diameter ≥4.0 cm, has been significantly associated with incident AF, stroke and death among individuals without AF 8 9. By contrast, studies including patients with AF not always confirmed the associations with adverse cardiovascular outcomes 10 11…”
Section: Introductionmentioning
confidence: 99%